Bridging Sorghum Yield Gap Through Up-Scaling Improved Technology in Wag-Himira Zone, Ethiopia - Mihiretu, Ademe; Assefa, Netsanet; Wubet, Adane (Agro Bali : Agricultural Journal, 2023)
Up-scaling of improved sorghum production practices (Sorghum technology, hereafter) was carried out for three years to bridge the yield gaps in dry-land areas. It was explicitly aimed to create wider technology demand among major stakeholders. Their roles and linkages were also acknowledged to make technology diffusion viable. The new technology was promoted for 264 farmers; planting and related agronomic practices were done as per the package. Results revealed that the new technology had a 116.6% yield advantage over the local sorghum production practice. The technological gaps among the new and local practice were 1400 and 988.7 kg ha-1 for grain and straw yields, respectively. The technological index (53.8%) also proved that sorghum production would increase through tamping the extension networks, on top of up-to-date technology usage. despite, 83.6% of the farmers were applied the full technology package, 68.3% of them described as it was tough due to its labor-intensive nature. Labor shortage, lack of experience and technological obscurity of studied farmers were defies for complete technology package use. To bridge sorghum yield gaps sustainably, the new technology should further scale-out to other similar areas via founding robust-enough stakeholder linkage, and demand-driven distribution.